2016
DOI: 10.3390/s16050708
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art in LP-WAN Solutions for Industrial IoT Services

Abstract: The emergence of low-cost connected devices is enabling a new wave of sensorization services. These services can be highly leveraged in industrial applications. However, the technologies employed so far for managing this kind of system do not fully cover the strict requirements of industrial networks, especially those regarding energy efficiency. In this article a novel paradigm, called Low-Power Wide Area Networking (LP-WAN), is explored. By means of a cellular-type architecture, LP-WAN–based solutions aim at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
146
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(156 citation statements)
references
References 23 publications
0
146
0
10
Order By: Relevance
“…Nonetheless, today, with the appearance of the commercial hardware and the sheer deployment of the LPWAN infrastructure, the situation starts to change. An overview of nine different LPWAN technologies has been reported in [6]. An overview of the LoRa technology is introduced in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, today, with the appearance of the commercial hardware and the sheer deployment of the LPWAN infrastructure, the situation starts to change. An overview of nine different LPWAN technologies has been reported in [6]. An overview of the LoRa technology is introduced in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Overview of nine different technologies has been done in Sanchez-Iborra and Cano, 8 while an overview focusing specifically on LoRa and Sigfox is introduced in Nolan et al 9 In Reynders et al, 10 the performance of the LoRa-like spread spectrum and Sigfox-like ultra narrowband (UNB) technologies are compared under interference. The simulation results revealed that for the applications which require higher throughput at relatively short range, the spread spectrum approach suits better than UNB.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline case is when all nodes are configured with LoRa common configuration consisting of transmission power of 14 dBm, carrier frequency of 915 MHz, spreading factor of 12, bandwidth of 125 kHz, and coding rate of 4/5. Except for the carrier frequency, this setting is similar to the baseline used in [10] and [13]. This baseline case is denoted as "default" in subsequent result figures.…”
Section: Baseline Casementioning
confidence: 98%
“…In this research, two network servers are employed: crowd-funded free service from The Things Network [13] and an open-source one based on LoRa Server [14]. While the former one is commonly used for DIY and non-profit community, we decided to also perform experiment with the latter one to be able to gain more control of the "Internet" side of this IoT system.…”
Section: Prototypementioning
confidence: 99%